The use of space geophysics data to establish a subsurface structural frameworks map on East Uweinat ring complexes province, Southwestern Desert, Egypt - Yaseen AAMER; Ashraf GHONEIMI; Salah HANAFY; Mohamed H. M. YOUSEF; Sara ZAMZAM (Contributions to Geophysics and Geodesy)
The study focuses on the east Uweinat area in the eastern sector of the Saharan continental crust and extends to the Arabian-Nubian basement rocks in the east. This area extends beyond the Egyptian territories, including the northern part of Sudan and the eastern part of Libya. The Saharan continental crust represents a challenge due to its classification as an arid to hyper arid environment and the difficulty of accessing it. The study aims to construct the regional structural framework of the basement complex that has its influence on the overlying sedimentary section, specifically in the part that belongs to the Saharan continental crust of Egypt. Space geophysical data was used, including GRACE, magnetic, SRTM Gravity Recovery and Climate Experiment, Earth Magnetic Anomaly Grid, Shuttle Radar Topographic Mission and geoid data. A qualitative and quantitative interpretation is used to highlight the subsurface geological picture and structure framework. The integration of these data helps to understand the subsurface structural framework and provide insights into the geological evolution of the region. The constructed structural framework map shows the presence of a large basin east of the Uweinat area, mainly sourced from the Nile River and a small amount of rainfall, with geological obstacles preventing water leakage out. The occurrence of the East Uweinat ring complexes and volcanism have both positive and negative impacts and must be taken into account in any systematic natural resources exploration strategy.